Entrepreneurship and Small Business - Burns Paul (Palgrave Macmillan, 2001)
This book addresses on of the major challenges facing society - how to encourage and develop entrepreneurial skills in a systematic way. Preface, David and Goliath, Heroes and Super-Heroes, Opportunity and Innovation, Start-Up, Start-Up: Making It Happen, Start-Up: Control and Decision-Making, E-Business, Developing a Business Plan, From Entrepreneur to Leader, Growth: Success, Growth: Take-Off, Financing Small Firms, The Family Firm, The Exit, Entrepreneurship Exercises, Index.